Windows server hacks - Tulloch, Mitch (O'Reilly, 2004)
One of the secrets to the ever-increasing popularity of Windows Server can be found in the simplicity its administration. The easy-to-use GUI, consistent set of tools, and wizards that walk you through complex tasks allow you to install, configure and maintain Windows servers without any knowledge of programming or scripting languages or learning complicated command-line syntax. It's possible, in fact, to accomplish about 90% of all Windows administration without ever opening a command prompt or running a script! But what about the other ten percent of the time? While it's true that most common, day-to-day tasks of Windows administration can be performed from the GUI, it's not always the best way, especially with complex or repetitive tasks Scripts and command-line tools often provide a faster, more flexible approach. Windows Server Hacks reveals techniques that go well beyond basic management tasks found in most handbooks to help busy system administrators master the more powerful features of Windows Server. Windows Server Hacks focuses on scripts and other tools that will make your life as an administrator much easier. These tools, or hacks--quick and dirty solutions to problems, or clever ways of doing things--were created by other professionals who've also had to struggle to find solutions to administering Windows environments. You'll save valuable time using their scripts, tools, tips, and advice. Plus, you can easily learn to customize the scripts to create even more powerful tools for your own, specific needs. The book includes secrets of the masters in such areas as Active Directory, User Management, Group Policy, DNS and DHCP, File and Print, IIS, performance and security. The hundred, industrial strength hacks in the book range from those that deal with general administration to more esoteric hacks in the areas of network deployment, patch management, and backup and recovery. No matter which Windows server you use--NT, IIS, 2000, or 2003--this book will put the knowledge and expertise of veteran system administrators and hackers to work for you. Windows Server Hacks will make your life easier while expanding your understanding of the capabilities of Windows Server.